Enhancement of chicken soup quality induced by low-voltage electrostatic field assisted stewing: a novel strategy for salt reduction - Zhenwei Wang; Che Shen; Di Liu; Qi Jin; Hongmei Fang; Xingyong Chen; Xingguang Chen; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Cellulose-based separators in aqueous zinc-ion batteries: Mechanistic strategies for dendrite suppression and performance enhancement - Yiyang Che; Chao Duan; Kang Yang; Xixi Di; Xiaoshuang Liu; Chuanyin Xiong; Mengxia Shen; Yonghao Ni (Carbohydrate Polymers, 2026)

A novel strategy for sodium reduction in salted goose: Employing basic amino acids to mitigate oxidation and improve sensory quality - Di Liu; Ran Wang; Zhenwei Wang; Che Shen; Qi Jin; Changhong Wu; Dekuan Wei; Kezhou Cai; Baocai Xu (Food Chemistry, 2026)

Microplastic ingestion and phthalate esters bioaccumulation in yellowfin tuna (Thunnus albacares): tissue-specific distribution across gills, stomach, and muscles - Ming-Huang Wang; Jeric B. Gonzalez; Chih-Feng Chen; Che-Jung Hsu; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2025)

Unraveling the flavor formation mechanisms of Wanxi dry-cured goose: Microbiomics, metabolomics, and flavoromics study - Ran Wang; Di Liu; Zhenwei Wang; Changhong Wu; Che Shen; Jingnan Lu; Wen Nie; Dekuan Wei; Kezhou Cai; Baocai Xu (Food Research International, 2025)

Corrigendum to “Improved entropy-CRITIC population model based on temporal and spatial variability: Construction and application in wastewater epidemiology” [Sci. Total Environ. 958 (2025) 177807] - Xinfeng Che; Xiaoyu Zheng; Wenjia Tao; Yu Zhang; Peipei Liu; Bin Di; Hongwei Qiao (Science of The Total Environment, 2025)

Mercury pollution control and Marphysa sanguinea bio-response in active-capped sediment with calcium alginate/activated carbon composite - Che-Jung Hsu; Ying-Chu Wang; Adrienne Chung; Cheng-Di Dong; Chiu-Wen Chen; Yu Ting; Hsing-Cheng Hsi (Journal of Hazardous Materials, 2025)

S-scheme heterojunction of WO3/metal-covalent organic frameworks for artificial photosynthetic CO2 reduction - Liang Fang; Li-Wen Bai; Di Wu; Hong-Tu Che; Yanxia Jiang; Ya Wang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2025)

Protecting mud crabs from pollution by microplastics, per- and polyfluoroalkyl substances, polycyclic aromatic hydrocarbons, pesticides, and heavy metals in mangroves - Wan Adibah Wan Mahari; Yiu Fai Tsang; Che-Jung Hsu; Hanafiah Fazhan; Youji Wang; Kianann Tan; Rock Keey Liew; Cheng-Di Dong; Khor Waiho; Su Shiung Lam (Environmental Chemistry Letters, 2025)

Molecular Epidemiology and Clinical Aspects of Dermatophytosis in Guiyang, Southwest China (2017–2023): A Single-Institution Retrospective Study - Songgan Jia; Jiali Zhu; Zhan Zhou; Wanglan Luo; Zhengling Shang; Yinhui Jiang; Clement K. M. Tsui; Di Che; Yanping Jiang (Mycopathologia, 2025)

Improved entropy-CRITIC population model based on temporal and spatial variability: Construction and application in wastewater epidemiology - Xinfeng Che; Xiaoyu Zheng; Wenjia Tao; Yu Zhang; Peipei Liu; Bin Di; Hongwei Qiao (Science of The Total Environment, 2025)

Tracking paddy rice acreage, flooding impacts, and mitigations during El Niño flooding events using Sentinel-1/2 imagery and cloud computing - Ruoqi Liu; Jinwei Dong; Yong Ge; Hui Lin; Xianghong Che; Yuanyuan Di; Xi Chen; Shuhua Qi; Mingjun Ding; Xiangming Xiao; Geli Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Evaluation of South Korean marine waste resources for hydrochar production: Effect of process variables - Tatwadhika Rangin Siddhartha; Elisa Kooy; Muhammad Kashif; Clovis Awah Che; Stef Ghysels; Di Wu; Frederik Ronsse; Philippe M. Heynderickx (Bioresource Technology, 2024)

Genotyping USA laboratory-maintained isolates and European clinical isolates of Dirofilaria immitis to assess macrocyclic lactone susceptibility or resistance at predictive SNP sites using droplet digital PCR - Sohini Kumar; Hua Che; Rafael Chiummo; Lea Heuer; Carolin Schneider; Margaret Werr; Frank Guerino; Elias Papadopolous; Anastasia Diakou; Andrei Daniel Mihalca; Donato Traversa; Angela Di Cesare; et al. (Veterinary Parasitology, 2024)

Insight into the autochthonous bacterial strains as starter cultures for improving the flavor profiles of dry-cured duck: Changes in microbial diversity and metabolic profiles - Xiao-min Li; Lie-hua Che; Wen-di Zhang; Qian-li Huang; Cong Li; Bao-cai Xu (Food Chemistry, 2024)

Novel Multiplexed High Throughput Screening of Selective Inhibitors for Drug-Metabolizing Enzymes Using Human Hepatocytes - Jianhua Liu; Daria Vernikovskaya; Gary Bora; Anthony Carlo; Woodrow Burchett; Samantha Jordan; Lloyd Wei Tat Tang; Joy Yang; Ye Che; George Chang; Matthew D. Troutman; Li Di (The AAPS Journal, 2024)

Characterization of CYP3A5 Selective Inhibitors for Reaction Phenotyping of Drug Candidates - Jie Chen; Lloyd Wei Tat Tang; Samantha Jordan; Makayla Harrison; Gabrielle M. Gualtieri; Ethan DaSilva; Danial Morris; Gary Bora; Ye Che; Li Di (The AAPS Journal, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Structurally diverse (9β-H)-pimarane derivatives with six frameworks from the leaves of Icacina oliviformis and their cytotoxic activities - Mingming Xu; Di Di; Lu Fan; Yingrun Ma; Xinyi Wei; Er-Xin Shang; Monday M. Onakpa; Oluwatosin O. Johnson; Jin-Ao Duan; Chun-Tao Che; Junfei Zhou; Ming Zhao (Phytochemistry, 2023)

Repeated applications of farm dairy effluent treated with poly-ferric sulphate did not adversely affect soil phosphorus availability, P fractions and pasture response — a 4-year field plot study - Xueying Che; Hong J. Di; Keith C. Cameron; Rosalind Dodd (Journal of Soils and Sediments, 2023)
Purpose Land application of farm dairy effluent (FDE) can cause phosphorus contamination of freshwater due to its high nutrient content especially phosphorus (P) in the animal dung. A novel FDE treatment technology has been developed that uses poly-ferric sulphate (PFS) to treat the FDE and recycle water for washing farmyard and reduce the risk of water pollution from P leaching from through the soil. It is important that the application of PFS-treated FDE (TE) does not cause any adverse impacts on soil fertility or plant growth when the TE is applied to the soil. Materials and methods A multi-year field plot study was conducted to determine the effect of repeat applications of FDE and PFS-treated FDE (TE) on soil P availability, P fractionations, plant yield and nutrient uptake. Eight applications of untreated FDE, TE and water as control were applied to replicated soil plots over the period of 4 years. The soil samples were collected on 1 December 2020, and nine pasture samples were harvested during the 2021–2022 dairy milking season. Measurements included soil chemical properties, soil phosphorous fractionations, plant biomass and plant phosphorus and nitrogen uptake. Results and discussion The results indicated that the majority of soil fertility indices and soil P fractions had no significant difference between the FDE and TE applications, with the exception of labile P which was significantly higher in the TE (122.7 mg kg −1 ) than in the FDE treatments (103.0 mg kg −1 ) at 0–10-cm soil depth and was also significantly higher in the TE (114.6 mg kg −1 ) than in the FDE treatments (74.0 mg kg −1 ) at 10–20-cm soil depth. Similarly, plant P uptakes and dry matter yields were also the same between the TE and FDE treatments with the average of being 54.4 kg P ha −1 and 12.8 t ha −1 , respectively. Conclusions Repeated applications of PFS-treated FDE had no adverse effect on soil P availability or plant growth when compared to untreated FDE application and had the potential to benefit soil fertility compared to control.

Thermodegradation characterization of microplastics: Dispersion effect and pyrolysis kinetics by artificial intelligence - Wei-Hsin Chen; Shih-Che Sun; Jherwin B. Ocreto; Thanh-Binh Nguyen; Su Shiung Lam; Young-Kwon Park; Cheng-Di Dong (Chemical Engineering Journal, 2023)

New Perspectives from Misdiagnosis: A Case of Primary Cutaneous Cryptococcosis Treated with Hydroxychloroquine Sulfate Successfully - Wanglan Luo; Di Che; Hongguang Lu; Yanping Jiang (Mycopathologia, 2020)

Calycosin-7-O-β-d-glucoside attenuates myocardial ischemia–reperfusion injury by activating JAK2/STAT3 signaling pathway via the regulation of IL-10 secretion in mice - Yujie Liu; Guoying Che; Zhixin Di; Weinan Sun; Jiawei Tian; Min Ren (Molecular and Cellular Biochemistry, 2020)

Suppression of Disheveled–Axin Domain Containing 1 (DIXDC1) by MicroRNA-186 Inhibits the Proliferation and Invasion of Retinoblastoma Cells - Xuanyi Che; Yuanjie Qian; Di Li (Journal of Molecular Neuroscience, 2018)

A study on the Dushiling tungsten-copper deposit in the Miao’ershan-Yuechengling area, Northern Guangxi, China: Implications for variations in the mineralization of multi-aged composite granite plutons - WenDi Chen; WenLan Zhang; RuCheng Wang; ZhuYin Chu; Rong Xiao; Di Zhang; XuDong Che (Science China Earth Sciences, 2016)